Effect of Precede–Proceed Model on Preventive Behaviors for Type 2 Diabetes Mellitus in High-Risk Individuals. (April 2017) - Moshki, Mahdi; Dehnoalian, Atefeh; Alami, Ali
This study sought to assess the effect of precede–proceed model on preventive behaviors for type 2 diabetes mellitus (DM) in high-risk individuals. In this semi-experimental study, 164 high-risk individuals for type 2 DM were selected and were randomly divided into two groups of intervention and control ( n = 85). Educational intervention was performed as a single session face-to-face instruction for 1.5 hr for the intervention group participants. Data were collected before (baseline) and immediately and 1 month after the intervention in the two groups. The mean score of predisposing (knowledge) factors ( p = .001), reinforcing factors ( p = .001), and enabling factors ( p = .02) were significantly different at baseline and 1 month after the intervention in the intervention group compared with the control group ( p < .05). A significant improvement occurred in the nutritional habits of high-risk participants in the intervention group at 1 month after the intervention compared with controls ( p = .001). The precede–proceed model can be effective for promoting the preventive behaviors for type 2 DM in high-risk individuals.